Living Sufism in the Tablighi Jamaat: A Hermeneutic Interpretation of Living Zuhd in Contemporary Indonesia - Nurhayati Nurhayati; Mukhlis Lubis; Suraya Attamimi; Surni Kadir (Jurnal Ushuluddin, 2025)
This study explores the practice of zuhd (asceticism) within the Tablighi Jamaat community in Palu, Indonesia, through the framework of Dilthey's hermeneutics. It attempts to interpret the subjective meaning of zuhd as a lived spirituality, rather than merely a doctrinal discipline, emphasizing how the Tablighi ethos of simplicity, resilience (tahammul), and detachment from politics reflects the enduring influence of Chishtiyya Sufism. The study employed qualitative methods with in-depth interviews and field observations, involving 15 informants from diverse backgrounds within the Tablighi Jamaat in Palu. Over a six-month observation period, the study employed Dilthey's dual interpretive model—verstehen (understanding the meaning) and erklären (explaining the context)—to uncover the inner experiences and ethical structures of zuhd among the participants. The main findings of this study indicate that the asceticism of the Tabligh Jamaat is characterized by (1) ritual movement (khuruj) as a spiritual discipline, (2) apoliticality as an ethical manifestation of separation, and (3) hospitality and humility as an extension of Chishtiyyah mysticism. This study concludes that Tabligh asceticism is a living form of Sufism, which shows the continuity of classical Chishtiyyah ethics in the contemporary Islamic da'wah movement. This study contributes theoretically to the hermeneutical understanding of Islamic asceticism and empirically enriches the study of spiritual practices in modern Muslim societies.